Commentary on: A European Consensus on the Consistent Use of the Term "Keratinocyte Cancer": Keratinocyte Cancer (KC) or Keratinocyte Skin Cancer (KSC) - Does the "S" Matter? - Konstantinos Seretis; Georgios Gaitanis; Ioannis D. Bassukas (Medical Journals Sweden, 2024)
Abstract is missing (Commentary)